Onrechtmatige Overheidsdaad for not Fulfilling Incentives for the Protection of Sustainable Food Agriculture Land - Riesta Yogahastama; Bahri, Syaiful; Mohammad Habib Ramdhani (JUSTISI, 2025)
The regulation of sustainable food agricultural land, especially regarding incentives as an effort to prevent high conversion of functions, the government has the authority to provide incentives as a form of determination from government officials regarding restrictions on agricultural land owned by the community. In practice, the provision of incentives by the government is often not fulfilled, resulting in injustice for the community, even though the regulations explicitly regulate the provision of incentives. this article aims to, How is legal protection for the community regarding incentives for the protection of Sustainable Food Agriculture Land? what is the model of lawsuit against government officials if compensation is not fulfilled in the protection of Sustainable Food Agricultural Land? The type of research used is legal research with statute approach, conceptual approach. This research is prescriptive in nature which aims to provide arguments for the results of the research that has been conducted. The results of this study indicate that legal protection for farmers if their incentives are not fulfilled has not been concretely regulated in Law Number 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land, besides that farmers in accessing justice experience difficulties due to the unregulated and also complicated arrangements regarding the provision of incentives. Also, when farmers experience losses from the non-fulfillment of incentives, they file a lawsuit for compensation, due to provisions that are not fulfilled by government officials as a result of the LP2B policy. Therefore, in law enforcement it is important to reconceptualize so that access to justice for people whose incentives are not fulfilled by the government can make claims against actions taken by the government. Keywords : Law Enforcement, Justice, Incentives